Consecutive Removal of Hazardous Dyes from Aqueous Solutions by Composite hydrogels Based on Rice Straw - E. Abdel-Aal, Samia; A. Mahmoud, Ghada; Elbayaa, A.A.; A. Badway, Nagwa; F. Ahmed, Doaa (Journal of Research Updates in Polymer Science, 2017)
The composite hydrogels based on rice straw (RS) and N-vinyl-2-pyrrolidone (NVP) or acrylamide (AAm) were successfully prepared by gamma irradiation. The effect of the radiation dose and the monomer content on the gel percent was studied. The composite hydrogels were confirmed by (FTIR), (TGA) and (SEM). It was found that the diffusion of water into the prepared composites was Fickian character. The removal of congo red (CR) and methyl orange (MO) dyes by (NVP/RS) and (AAm/RS) composite hydrogels were investigated as a function of the pH, contact time, initial dye concentration solution and temperature. It was achieved that the adsorption capacity of (NVP/RS) composite hydrogel towards (CR) and (MO) was higher than (AAm/RS) one. The kinetic data was tested by the pseudo-ﬁrst-order and the pseudo-second-order kinetic models. The adsorption isotherm was closely fitted with the Freundlich model for adsorption of CR and MO onto (NVP/RS) and the Langmuir model for adsorption of the dyes onto (AAm/RS). A high adsorption capacity was obtained in the second adsorption cycle of MO onto the composite hydrogels loaded with CR. Improvement in the adsorption of MO onto (NVP/RS) and (AAm/ RS) composite hydrogels loaded with Co(II).